Pro-apoptotic effect of Persea americana var. Hass (avocado) on Jurkat lymphoblastic leukemia cells (2014)
ABSTRACT: Context: Therapy for leukemia has a limited efficacy. There is a need to search for alternative anti-leukemia therapies. Persea americana Mill var. Hass (Lauraceae) is a tropical fruit (avocado) that might be used against cancer. Objective: To investigate whether P. americana induces death in Jurkat lymphoblastic leukemia cells. Materials and methods: Four ethanol extracts (0.1, 0.5, 1, 2 and 5 mg/mL) from avocado fruit (endocarp, whole seed, seed and leaves) were analyzed against Jurkat cells. Hydrogen peroxide generation by oxidation of 20,70 -dichlorodihydrofluorescein diacetate to the fluorescent compound 20 ,70 -dichlorfluorescein assay, acridine orange/ethidium bromide staining, flow cytometry analysis of annexin-V/7-amino-actinomycin, mitochondrial membrane potential and immunocytochemistry detection of transcription factor p53, caspase-3 and apoptosis-inducing factor (AIF) were evaluated. Results: Endocarp, seed, whole seed, and leaf (0.1 mg/mL) extracts induced significant apoptosis in Jurkat cells (p50.001) in an oxidative stress-dependent fashion via mitochondrial membrane depolarization (52–87%), activation of transcription factor p53 (6.3–25.4%), protease caspase-3 (8.3–20%) and predominance of AIF reactivity (20.6–36%) in all extracts. Similar results were obtained with 0.5 mg/mL extracts. However, extract 1 mg/mL concentration induced necrosis (100%). Conclusions: P. americana extracts function as a pro-apoptotic compound. Leukemic cells are eliminated through an oxidative stress mechanism. This study contributes to the understanding of the molecular mechanism of the avocado and its therapeutic action on leukemia.